Let your students cheat on mathematics online exams: students’ perspectives - Nurdin, Erdawati; MZ, Zubaidah Amir; Nufus, Hayatun; Thakur, Deepti; Shah, Firdous A.; Dube, Rakesh; Wijaya, Tommy Tanu (Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
The Covid-19 outbreak has an impact on the provision of education. One of them is the process of online assessment or examination. Difficulties occur during online exams; weak supervision can increase cheating behavior among students. Generally, teachers or lecturers think about how to prevent this behavior. However, what if they are allowed to